Early Experience with Unsedated Ultrathin 4.9 mm Transnasal Gastroscopy: A Pilot Study. (2008) - Cheung, Justin; Bailey, Robert; van Zanten, Sander Veldhuyzen; McLean, Ross; Fedorak, Richard N; Morse, John; Millan, Mario; Guzowski, Tom; Goodman, Karen J; for the CANHelp working group,
Abstract : BACKGROUND: Unsedated transnasal gastroscopy is a technique with unverified clinical advantages. OBJECTIVE: To evaluate the efficacy and procedure times with transnasal gastroscopy by physicians with no previous experience in transnasal endoscopy. METHODS: Unsedated transnasal gastroscopy using 4.9 mm ultrathin transnasal gastroscopes with randomization to two different biopsy forceps was prospectively evaluated during a single day in January 2008. The outcomes included patient tolerance (scale: 1, no discomfort; 10, severe discomfort), physician technical assessment (1, excellent; 10, very poor), gastric biopsy quality, adverse events and procedure times. RESULTS: Twenty patients underwent transnasal gastroscopy. Nineteen patients (95%) successfully completed transnasal gastroscopy. The patient-reported mean (± SD) overall discomfort level during the procedure was 4.0±1.9 compared with a physician-estimated level of 3.2±1.7 (P=0.04). Only 10% (n=2) reported they would have preferred sedated over unsedated gastroscopy. Mean total encounter time from anesthesia to discharge was 33.5±9.3 min. The time from anesthesia to insertion was 7.0±5.3 min and from room exit to discharge 6.2±2.9 min. No patients who had gastric biopsies taken (zero of 14) had any of unacceptable quality. The only adverse event was distressing sensations (dyspnea, dizziness) in one patient that started during pre-endoscopy anesthetic application, persisting postendoscopy, but without any abnormalities in vital signs. CONCLUSION: Assuming the adverse event was a rare reaction, early experience with unsedated ultrathin transnasal gastroscopy was an efficient, effective and well-tolerated procedure for evaluation of the upper gastrointestinal tract.